A parameter self-correcting thermal network model considering IGBT module solder layer aging. (April 2023) - Liu, Yulin; Du, Mingxing; Yin, Jinliang; Dong, Chao
Abstract: A parameter self-correcting thermal network model is proposed in this paper, and then the accurate junction temperature of the IGBT solder layer after aging is calculated. Considering that the voids and cracks generated by the aging of the solder layer of the IGBT module affect the parasitic capacitance and common mode interference signal of the power supply circuit in which it is located, the common mode interference signal of the IGBT module can be monitored for the aging state of the solder layer. When the IGBT module solder layer is aging, the thermal resistance and thermal capacity of the thermal network model are calculated based on the common-mode interference signal, and the thermal network model is modified to calculate the exact junction temperature. The major advantage of this method is that the online self-correction of the thermal network model parameters can be realized. Finally, the correctness and effectiveness of the proposed method are confirmed by simulation and experiment.